Random forest-based modeling for insights on phosphorus content in hydrochar produced from hydrothermal carbonization of sewage sludge. (15th April 2022) - Djandja, Oraléou Sangué; Salami, Adekunlé Akim; Wang, Zhi-Cong; Duo, Jia; Yin, Lin-Xin; Duan, Pei-Gao
Abstract: The hydrochar produced from hydrothermal carbonization(HTC) of sewage sludge (SS) usually has a high phosphorous (P) content, and that would result in fouling and energy efficiency reduction. Therefore, it is important to monitor the P content during the hydrochar production process. This work suggests a data-driven Random Forest-based model to predict the total P content in the hydrochar (TP-hc) from the HTC of SS. Various configurations of inputs features were examined, including the data of proximate analysis, ultimate analysis, ultimate and proximate analyses, and for each configuration, either if the total P in the SS (TP-ss) was known or not. Overall, the models including TP-ss as input have accurately predicted the TP-hc with an R 2 located in [92–95%]. Features' importance approach and partial dependence analysis pointed out that the TP-ss, ash content, reaction temperature (T), reaction time (t), and initial pH of feedwater exhibit positive effect on the TP-hc. In contrast, contribution of the volatile matter (VM) of SS was mostly negative. Dry matter loading exhibits no obvious monotonicity with TP-hc. This work could guide the production of SS-hydrochar with the desired P content, and thus avoid time and resources consuming for many trials. Graphical abstract: Image 1 Highlights: Random Forest model is proposed to predict the phosphorus (P) content in hydrochar. Various configurations of inputs features were investigated. Predictors' partial importance were explored using game theory-based method. The P content of sewage sludge is the most influential predictor. R 2  > 0.92 is obtained when P content in sewage sludge is among predictors.